Association of probiotic use with nivolumab effectiveness against various cancers: A multicenter retrospective cohort study - Junya Arai; Ryota Niikura; Yoku Hayakawa; Nobumi Suzuki; Tetsuro Honda; Takuma Okamura; Kenkei Hasatani; Naohiro Yoshida; Tsutomu Nishida; Tetsuya Sumiyoshi; Shu Kiyotoki; Takashi Ikeya; et al. (Cancer Medicine, 2023)
Abstract Background Previous studies have revealed an association between probiotic use and effectiveness of immune checkpoint inhibitors in renal and lung cancers. However, little is known regarding other cancers, including gastrointestinal cancer. Methods To address this issue, we conducted a multicenter retrospective cohort study and the duration of nivolumab treatment for various cancers was compared between probiotic users and non‐users. Results and Conclusions In total, 488 patients who received nivolumab therapy were included. In all cancers, no significant differences in treatment duration of nivolumab were observed between probiotic users and non‐users (median 62.0 vs. 56.0, hazard ratio = 1.02, p = 0.825), whereas probiotic use, compared with non‐use, in patients with gastric cancer was significantly associated with a longer duration of nivolumab treatment (55.0 vs. 31.0 days, hazard ratio = 0.69, p = 0.039). In conclusion, probiotics may improve the response to nivolumab and potentially prolong progression‐free survival in patients with gastric cancer.